Tree community dynamics in a forest adjacent to the reservoir of a hydroelectric power plant in the southern Brazilian Atlantic forest Dinámica de la comunidad de árboles en un bosque adyacente al reservorio de una central hidroeléctrica en la mata atlántica del sur de Brasil - Fuck Valim B.D.* (2018)
© 2018, Universidad Austral de Chile. All rights reserved.This study aimed at analyzing the dynamics of tree components in a forest adjacent to the Barra Grande Hydroelectric Power Plant reservoir, in the southern Brazilian Atlantic Forest, located in the municipality of Capão Alto. In 2013, this area was previously inventoried and divided into three sectors according to the distance from the reservoir: lower sector (in contact with the reservoir), intermediate sector (a slope area following the first sector) and upper sector (near the slope top). Fifty plots were allocated in the sectors, where all tree individuals with DBH (diameter at breast height) higher than or equal to 5 cm were inventoried (identified and measured at the circumference). In 2017 the surviving individuals were measured again, the dead ones were registered and the recruits (those with DBH reaching 5 cm) were included into the survey. Dynamics rates in number of individuals and basal area were calculated. The tree community under study has shown species richness stability, though also structural development, which is typical of areas that are facing a self-thinning process. The higher density populations of each sector have shown a similar structural dynamics pattern. There were no differences in the demographic rates among sectors, indicating that, approximately 12 years after the reservoir filling, the forest dynamics has not been influenced by the reservoir but by ecological factors dependent on density, such as competition.